The impact of Blockchain on retail banking - Marques, Eduardo João Serrubeco (2020)
Banking has been at the forefront of financial innovation for many years. The financial industry, especially retail banks, have not had any outside contenders capable of really threatening what are the main functions of banks, getting deposits, lending money and serve as the leading financial intermediary on transactions. These functions have been solely a banking business for many years, though since the 2008 Financial Crisis, this status quo suffers a big reverse. In this scenario, Bitcoin’ underlying technology raises attention as its potential is acknowledged and its increasingly regarded as a challenge for the financial system. This study aims to empirically access what has been the effect so far of the Blockchain technology on the retail banking sector and contribute to the ongoing discussion of whether this technology is disrupting or giving a competitive advantage to banks. First, the technicalities of this technology are analyzed to give a broad picture of how this technology works and to isolate the differentiator factor. Second, this study analyzes the present and future impacts, advantages, and shortcomings in a practical and business-oriented way. Lastly, through regression analyses, this study tries to take empirical evidence on which has been the effect of this technology. The empirical evidence only concerns the retail banking significant sample of the US retail banking sector. The results are not consistent between the two models used. There are some limitations on this study such as the lack of data available and quality models capable of measure accurately the blockchain impact on retail banking. However, on both there is what might be an indication that this technology impacts negatively banking, meaning, it is disruptive.